Evaluation of pollutant emissions generated at bus stops - Ozener, Orkun; Gezer, Onur; Ozkan, Muammer (ELSEVIER SCI LTD, 2022)
Public transport is the transport alternative preferred by many people for daily activities. Especially bus rapid transit (BRT) systems are very popular in terms of time management. Nearly a million of passengers use Metrobus line (Istanbul BRT system) daily. In average 7160 daily bus services are realized on this line. During rush hours, due to the short time intervals between consecutive buses and passenger crowd there are several buses at the station at the same time. Vehicles are operated at idling during this time followed by a high engine load at takeoff motion period. The amount of fuel injection into the cylinder increase at the take-off period. High engine load operation condition increases engine exhaust emissions. On the other hand, the conversion efficiency of after-treatment equipment deteriorates at non-load idling operation at the bus stops because the exhaust gas temperature decreases. Thus, excessive levels of pollutants are emitted in these areas where human population density is so high. Within the scope of this study, the emissions were evaluated at the stations of Istanbul BRT system. The results showed that a substantially amount of emissions are released during bus take-off which can be dangerously harmful to urban population. Also positive effects of an acceleration limitation to be created depending on the total weight and road grade was shown in this study.
Keywords: Real driving emissions; Bus stops; Take-off regime; Fuel consumption; Public transport; Diesel engine; DUTY DIESEL-ENGINE; RAPID-TRANSIT; NOX EMISSIONS; TRANSPORTATION; IMPACT; MODEL; FUELS; CYCLE; N2O; Energy & Fuels; Engineering